World’s first indoor ai-based vertical berry farm in Virginia:revolutionizing agriculture with 90% water savings - Thirunahari Ugandhar, Dr. (International Journal of Biological Research, 2024)
The establishment of the world’s first AI-based indoor vertical berry farm in Virginia, USA, marks a pivotal advancement in agriculturaltechnology, integrating artificial intelligence (AI) with innovative vertical farming techniques. This facility, spanning 1081 acres and utilizing 30-foot-high towers, redefines traditional agricultural practices by optimizing space and resource use, enabling food production inurban environments where conventional farming may not be viable. Vertical farming allows for the cultivation of crops in stacked layers,effectively addressing land scarcity and reducing transportation costs while enhancing food security.The AI-driven management system at the Virginia facility plays a crucial role in regulating essential growth factors such as temperature,light, humidity, and nutrient delivery. By continuously monitoring these parameters and adjusting them in real time, the system ensuresoptimal conditions for plant development, leading to healthier crops and superior berry quality. One of the standout features of this innovative farm is its remarkable water-saving capability; the AI technology facilitates a 90% reduction in water usage by delivering preciseamounts of water only when needed. This efficiency is particularly significant given the growing global challenges of water scarcity andthe need for sustainable agricultural practices.Furthermore, this AI-based approach utilizes 17% less land compared to traditional farming methods, underscoring its potential as a highlyefficient model for future food production. With its commitment to resource conservation and enhanced productivity, this vertical farminginitiative exemplifies how technology can revolutionize agriculture, offering promising solutions to meet the increasing demand for foodwhile minimizing environmental impact. As the world grapples with pressing issues related to food security and environmental sustainability, the Virginia vertical berry farm stands as a beacon of innovation, paving the way for the future of agriculture.